Community-based water resource management in North-west Cameroon: the role of potable water supply in community development. Issue 2 (4th May 2017) - Tantoh, Henry Bikwibili; Simatele, Danny
Abstract: This paper examines the role of community-based water resource management in community development in Cameroon. Natural resources across sub-Saharan Africa (SSA) have been managed from centralized systems and this has resulted into massive marginalization and disenfranchisement of rural communities. However, there is now a shift in policy interventions towards adopting pro-community approaches in resource management. Although this paradigm is increasingly becoming common, key questions on how to propagate the participation of the most vulnerable members of a community and the impact on community development remain pertinent. Using both secondary and empirical data collected though tools inspired by the traditional of participatory research; it is argued in the paper that community-based natural resource management (CBNRM) has the potential to imbue the full participation of local people in any development issues and changes rural societies and communities in sub-Saharan African countries. Rural Cameroon, like many other rural regions in sub-Saharan Africa faces a myriad of challenges, among which include water resource governance. This paper therefore, explores the role of CBNRM in sustainable management of potable water resources. This has been explored within contemporary theoretical and development debates on natural resource management in developing countries.